Meningkatkan Hasil Belajar Materi Pengurangan Dan Penjumlahan Pecahan Melalui Permainan Monopoli - safira Nurmuliasari (PGSD FKIP UPR, 2023)
The purpose of this study is to describe the improvement of learning outcomes, and describe teacher activities and student activities of subtraction and additionof fractions with monopoly games in grade IV of the 2022/2023 MIN 2 school year Palangka Raya City.This study uses the Kemmis and Mc. Taggart model of Classroom Action Research (PTK), which was carried out by grade IV teachers of MIN 2 Palangka Raya City.The research was carried out as many as two cycles, each cycle there were three meetings. The subjects of this study were class IV E students totaling 25 students. The data collection techniques carried out are tests and observations. Data analysis techniques are carried out quantitatively and qualitatively. The results showed that there was an increase in the learning outcomes of subtraction and addition material. The average learning outcomes of the class in the initial test data (pretest) there were 3 or 12% of students completed with an average score of 50.84, in cycle I there were 14 or 56% % of students completed with an average score of 75.6, then in cycle II There are 25 or 100% complete students with an average score of 86.4 and in the final test data (postest) there are 25 or 100% complete students with an average score of 94.28. Forteacher and student activities in the first cycle the good category and in the second cycle increased to the very good category.